Human rights in the field of comparative education - Biseth, Heidi; Holmarsdottir, Halla B. (Comparative and international education (Sense Publishers), 2013)
There is no single answer to the question: what are human rights? The answer depends on whom you ask. Several of the papers presented at Fourteenth World Congress of Comparative Education held at Bogaziçi University in Istanbul, Turkey, in June 2010 discussed issues related to human rights from a comparative education viewpoint. The nine papers presented in this book spans from policy analysis to practices in classrooms. They include analyses of human rights from a regional or country perspective, including Greece, Jordan, the Latin American region, Morocco, Northern Ireland, Portugal, the UK,